Correlating outgassing and smoke phenomenon in electron beam powder bed fusion of Ti6Al4V using a residual gas analyzer - Ye, Jihui; Chen, Tiejue; Körner, Carolin (Progress in Additive Manufacturing, 2024)
Electron beam powder bed fusion (PBF-EB) is an additive manufacturing technique that fabricates customized components using an electron beam in a controlled vacuum environment. Maintaining high vacuum quality is crucial to prevent feedstock contamination. However, the inherent nature of the PBF-EB process introduces a gas load into the system, potentially affecting process stability and product quality. This study utilizes a residual gas analyzer to investigate experimentally outgassing associated with various process activities, including electron beam radiation, rake movement, and powder outgassing. The findings indicate that hydrogen, water, nitrogen, oxygen, argon, and carbon dioxide are the predominant gases present during PBF-EB processes. Moreover, rapid outgassing is identified as a likely trigger for powder movement, marking the initial stage of the smoke phenomenon. These results contribute fundamental insights into the gas atmospheres in PBF-EB processes.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Electron beam powder bed fusion (PBF-EB); Outgassing; Process monitoring; Residual gas analysis; Smoke effect